Potential Deleterious Effects of L-Citrulline Supplementation in Isoproterenol-Induced Myocardial Infarction: Focus on Nitrosative Stress - Gregorius Bhaskara Wikanendra; Wawaimuli Arozal; Kusmardi Kusmardi; Vetnizah Juniantito; Andrea Laurentius (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
L-Citrulline shows potential activity as a supplement to prevent myocardial infarction through vasodilative and possible antioxidative effects but may be deleterious by causing nitrosative stress. This study determined the potentially deleterious effects of L-citrulline supplementation in isoproterenol-induced myocardial infarction with a focus on nitrosative stress. L-Citrulline supplementation was given orally at dosages of 300 or 600mg/kg body weight daily for 6 days. Myocardial infarction was induced in Wistar rats via subcutaneous injection of isoproterenol (85 mg/kg body weight (BW)) on day 4 and 5. Blood pressure was measured at the end of the study (day 6) and rats were sacrificed to collect heart tissue samples for a histopathological evaluation. The histopathological evaluation was done using hematoxylin and eosin staining for the myocardial damage evaluation and immunohistochemical (IHC) staining of arginase-2, inducible nitric oxide synthase (iNOS), and 3-nitrotyrosine to evaluate nitrosative stress. L-Citrulline supplementation failed to show a significant protective effect on blood pressure and exacerbated the decrease of diastolic blood pressure. Both low and high dose L-citrulline supplementation had a significant protective effect on myocardial damage compared to the isoproterenol group (p<0.01). L-Citrulline also caused increased nitrosative stress as shown by increased expression of arginase-2 and 3-nitrotyrosine on IHC staining but tended to show an ameliorative effect on iNOS expression. A significant increase in arginase-2 expression was detected between the high dose group and the other groups (p<0.01 vs. normal and isoproterenol groups; p<0.05 vs. low dose group). L-Citrulline supplementation increased 3-nitrotyrosine expression in a dose-dependent manner, which was significantly different compared to the normal group (low dose: p<0.013; high dose: p<0.003). L-Citrulline increased the production of nitrosative stress but resulted in less myocardial damage through its other effects.